2015
DOI: 10.17221/8079-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Association of a synonymous mutation of the PGAM2 gene and growth traits in rabbits

Abstract: Phosphoglycerate mutase (PGAM2) catalyzes the conversion of 3-phosphoglycerate into 2-phosphoglycerate and releases energy during glycolysis in muscle tissues. PGAM2 has been considered as a candidate gene to influence growth, development, and carcass traits in livestock. The aim of this study was to investigate the association between polymorphisms of PGAM2 and growth traits in rabbits. Three single nucleotide polymorphisms (SNPs) were identified by direct sequencing in 20 random individuals from three breeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…Wu et al . [ 11 ] observed that no association was found between PGAM and BW at market. Sternstein et al .…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al . [ 11 ] observed that no association was found between PGAM and BW at market. Sternstein et al .…”
Section: Discussionmentioning
confidence: 99%
“…In China, Zhang et al (2012) found significant associations (P<0.05) between growth hormone receptor gene (GHR) and body weights in Tianfu Black, Ira and Champagne rabbits. Additionally, Wu et al (2015) reported significant association (P<0.05) between phosphorglycerate mutase gene (PGAM2) and growth traits in the same Chinese rabbit breeds. The differences between genotypes of GH gene in ½A½M cross rabbits were significant (P<0.05) in all body weights except body weight at 4 weeks and the CC genotype was absent ( Table 10).…”
Section: Polymorphic Associations Between Genotypes Of Gh Gene and Grmentioning
confidence: 98%
“…There were significant associations between the genotypes SNP and body weights. In this concept, the growth hormone gene (GH) located on chromosome 19, growth hormone receptor gene (GHR) located on chromosome 11, progesterone receptor gene (PGR) located on chromosome 1, fibroblast growth factor gene (FGF) located on chromosome 3, insulin-like growth factor 1 and 2 genes (IGF1and IGF2) located on chromosome 4, myostatin gene (MSTN) located on chromosome 7 and melanocortin 4 receptor gene (MC4R) located on chromosome 9 have shown significant associations with body weighs in rabbits (Inoue et al, 2006;Fontanesi et al, 2008;Lu et al, 2011;Zhang et al, 2012;Fontanesi et al, 2012;Peng et al, 2013;Sahwan et al, 2014;Wu et al, 2015;Othman et al, 2015;El-Aksher et al, 2016;El-Sabrout and Aggag, 2017;Migdal et al, 2018). The growth hormone gene (GH) alters the metabolism of carbohydrates, proteins and lipids and promotes postnatal growth of mammals exerting direct or indirect effects on numerous tissues (Fontanesi et al, 2012).…”
mentioning
confidence: 99%
“…HOLSINGER and WEIR (2009) revealed that the importance of discovery a large number of SNPs in the genomes from several species that has enabled exploration of genome-wide signatures in selection via an assessment of variation in marker allele frequencies among these populations. Genes associated with productive traits have been identified using single nucleotide polymorphisms of many candidate genes (ZHANG et al, 2013;WU et al, 2015). It is recognized that the egg production traits of chickens are controlled by a complicated multiple genes (GU et al, 2011).…”
Section: Introductionmentioning
confidence: 99%